The role of nuclear weapons in Russia's strategic deterrence: Implications for European security and nuclear arms control - Lydia Wachs (Stiftung Wissenschaft und Politik (SWP), 2022)
In the West, Russia's nuclear deterrence strategy is often described as one of 'escalate to deescalate'. The thinking goes that Moscow is prepared to use nuclear weapons at an early stage in a conflict in order to 'deescalate' and terminate the confrontation quickly in its favour. However, Russia's official military doctrine, nuclear exercises of the Russian military, and debates among political and military elites have so far pointed in a different direction. With the concept of 'strategic deterrence', Russia has developed a holistic deterrence strategy in which nuclear weapons remain an important element. Yet, to gain more flexibility below the nuclear threshold in order to manage escalation, the strategy also conceptualises a broad range of non-military and conventional means. Given Russia's dwindling arsenal of conventional precision weapons due to its war against Ukraine as well as the strategic adaptation of the North Atlantic Treaty Organization (NATO), Russia's strategy is likely to change: In the coming years, Russia's reliance on its non-strategic nuclear weapons will probably increase. These developments could both undermine crisis stability in Europe and further impede the prospects for nuclear arms control in the future.
Keywords: 320; nuclear weapons; strategic deterrence; Russia; strategic deterrence; military doctrine; North Atlantic Treaty Organization (NATO); war against Ukraine